The Medium Is the Measure: Technical Change and Employment, 1909—1949 - Alexopoulos, Michelle; Cohen, Jon (The Review of Economics and Statistics, 2016)
New indicators, based on technology titles, are used to measure the impact of innovative activity on the U.S. labor market between 1909 and 1949. We find that positive technology shocks raised productivity, employment, vacancies, and labor turnover and lowered unemployment and business failures. Moreover, automotive and electrical innovations (quintessential general-purpose technologies) had a greater positive impact on employment than those in mechanical innovations. The overall results, compatible with the predictions of the real business cycle model, raise questions about the anemic recovery in employment after 1934 since the strong upsurge in technical change failed to be accompanied by vigorous job expansion.